Creating Profile of Kalurahan Kebonharjo, Kapanewon Samigaluh, Kabupaten Kulon Progo, using Community Participation Method - Kurniati, Ayu Candra; Septiana Fathurrohmah (ReTII, 2024)
Rural development in Indonesia has currently received special attention from the government. The importance of village data in the rural development planning process means that ruralâ€™s governments must strive to provide data related to the specific characteristics of their area. This can be realized in the making of rural profile. Implementation stages include preparing instruments, forming working groups, collecting and validating data assisted by the community (a form of participation activity). Furthermore, data processing will be carried out through clarification, tabulation, compilation and recapitulation either through application programs or manually. The final stage is publication which will be carried out via online media. Kebonharjo sub-district consists of 10 pedukuhan, has an area of â€‹â€‹746.92 hectares, population of 2,376 people with the main source of income is in agriculture. Geographically, Kalurahan Kebonharjo has most of the landforms tend to be hilly with an average land slope of 38 degrees. The Kebonharjo’s potential are from agriculture sector, tourism, the presence of UMKM and culture preservation.